2002
DOI: 10.1103/physrevb.66.035306
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and noise in adiabatic quantum pumps

Abstract: We investigate the distribution function, the heat flow and the noise properties of an adiabatic quantum pump for an arbitrary relation of pump frequency ω and temperature. To achieve this we start with the scattering matrix approach for ac-transport. This approach leads to expressions for the quantities of interest in terms of the side bands of particles exiting the pump. The side bands correspond to particles which have gained or lost a modulation quantumhω. We find that our results for the pump current, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
616
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 372 publications
(631 citation statements)
references
References 61 publications
13
616
1
1
Order By: Relevance
“…Then Zhu and Wang developed the Floquet scattering method to study the pumping with a series of time-periodic potentials, their main results in both the weak pumping and strong pumping regimes being consistent with experiment results [16]. Moskalets and Büttiker generalized the Floquet scattering theory to the quantum pumping in mesoscopic conductors [17]. Kim found that the Floquet scattering approach and the adiabatic scattering approach give the exactly equivalent result under the weak pumping condition for a double delta-barriers model [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then Zhu and Wang developed the Floquet scattering method to study the pumping with a series of time-periodic potentials, their main results in both the weak pumping and strong pumping regimes being consistent with experiment results [16]. Moskalets and Büttiker generalized the Floquet scattering theory to the quantum pumping in mesoscopic conductors [17]. Kim found that the Floquet scattering approach and the adiabatic scattering approach give the exactly equivalent result under the weak pumping condition for a double delta-barriers model [18].…”
Section: Introductionmentioning
confidence: 99%
“…The spin-dependent electrical current pumped into the lead can be expressed in terms of the Floquet scattering matrix S s F of the lead as [17,40] …”
Section: Spin Pumping With Tr Symmetrymentioning
confidence: 99%
“…[37]. Given all the transmission and reflection amplitudes t R/L,j and r R/L,j , the dc part of the current in, say, the right lead is given by [22,23] …”
Section: Charge Pumping On An Infinite Linementioning
confidence: 99%
“…With the exception of a few papers [22,[24][25][26][27]49], the earlier studies of charge pumping have generally considered systems in which oscillating potentials are applied to two or more sites. In such cases, it is known that if the oscillation frequency ω is small, the dc part of the pumped current is proportional to ω; the charge pumped per cycle (with time period 2π/ω) therefore has a finite value in the adiabatic limit ω → 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation